An updated checklist of the hoverflies (Diptera: Syrphidae) of Slovenia - Kočić, Anja; Vujić, Ante; Tot, Tamara; Milosavljević, Marina Janković; Groot, Maarten De (Zootaxa, 2023)
This paper is an updated checklist of the hoverflies of Slovenia. Since the last checklist of 274 species published by de Groot & Govedič in 2008, a large number of additional specimens have been collected and studied. In the present study, 42 species are reported for the first time for the Slovenian hoverfly fauna. Sphegina sublatifrons Vujić, 1990 is deleted from the Slovenian list. In total, 362 species from 77 genera are reported. According to the IUCN European Red List of Hoverflies, 29 species are classified as Endangered, 9 as Vulnerable, 19 as Near Threatened, 302 as Least Concern and 3 as Data Deficient. The distribution of species per region in Slovenia is presented. With 243 species, Upper Carniola hosts the largest number of registered species, followed by Central Slovenia (233 spp.), Gorizia (230 spp.), Savinja and Littoral Inner-Carniola (both with 173 spp.), Coastal-Karst (133 spp.), Southeast Slovenia (71 spp.), Drava (60 spp.), Carinthia (56 spp.), Lower Sava (52 spp.), Mura (47 spp.) and Central Sava (8 spp.). A significant increase in the number of new records has been noted in recent decades, and the possible reasons for this trend are also discussed here.